Imaging and Manipulation of Adsorbates Using Dynamic Force Microscopy Proceedings from the AtMol Conference Series, Nottingham, UK, April 16-17, 2013 - Moriarty, Philip; Gauthier, Sebastien (Advances in Atom and Single Molecule Machines, 2015)
Imaging and Manipulation of Adsorbates using Dynamic Force Microscopy provides an overview of the latest developments in dynamic force microscopy (DFM) of atoms, molecules, and nanoparticles adsorbed on solid surfaces. Significant advances in the capabilities of this technique have been made in the last decade and this book represents a timely snapshot of the major research themes in the field, with a particular focus on the manipulation of matter at the atomic and (sub)molecular levels. This edited volume will be of keen interest to researchers active in nanoscience and its various sub-fields including, in particular, scanning probe microscopy.  This book expands on the previous volumes in the series Advances in Atom and Single Molecule Machines.